Modification of eating habits and lifestyle during COVID-19 in university students from Mexico and Peru - Arispe-Alburqueque, Claudia Milagros (2024)
Objective: It was to evaluate changes in lifestyle habits and health behavior among university students in Peru and Mexico during periods of confinement associated with the COVID-19 pandemic and to identify possible relationships between these changes and sociodemographic variables, health status, and technology consumption. Methods: It was a quantitative, observational, and cross-sectional study conducted among a population of 739 Mexican students and 305 Peruvian students, most of whom were women (n =778, 74.5%) and non-graduates (n =921, 88.2%). The questionnaire scale for changes in lifestyles during the quarantine period has been previously validated. Results: The association between sociodemographic factors and dimensions of change in healthy lifestyles was evaluated, and it was shown that gender and country of residence were significant for all dimensions of healthy lifestyle (p < 0.05), except for the level of education, which did not show significance about the change in the dimensions of media consumption (p = 0.875) and physical activity (p = 0.239). Within the dimensions mentioned, it can be stated that women are more likely than men to change their eating habits (adjusted prevalences (aPR) = 1.08, p < 0.001), media consumption (aPR = 1.04, p < 0.001), and physical activity (aPR = 1.02, p < 0.001). Meanwhile, participants from Peru are more likely than participants from Mexico to change physical activity (aPR = 1.14, p < 0.001) and media consumption (aPR = 1.22, p < 0.001). Finally, graduate students were more likely than undergraduate students to change eating habits (aPR = 1.09, p = 0.005) and unhealthy habits (aPR = 1.06, p = 0.030). Conclusion: It was concluded that there were lifestyle changes in Mexican and Peruvian university students in their eating habits, physical activity, internet consumption, and food delivery.